LAWANG SEWU DALAM SUDUT PANDANG GEOMETRI - dkk, Utari Oktaviani (Jurnal Pendidikan Matematika, 2019)
LAWANG SEWU IN GEOMETRY VIEW. Mathematics and culture are two things closely related. But sometimes mathematics is seen as something that is not connected to everyday life. Infactthe environment can be a source of mathematical problems in real life. The environment is one of culture, one of which includes historic buildings. Mathematics in culture is referred to by the term ethnomatematics. Lawang Sewu is one of the historical buildings located in the city of Semarang. The purpose of this research is to know the geometry structure of Lawang SEWU building. This building can be used as a research object with qualitative descriptive method, with data collection using direct observation on research object, interview with speaker, and using library study related to research This. Through research that the authors have done, it can be concluded that Lawang SEWU building has a geometry structure of space, namely cube, beam, Limas, and Octagonal prism.